1985
DOI: 10.1016/0014-5793(85)80045-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in the cell binding region of human fibronectin molecules isolated from cultured normal and tumor‐derived human cells

Abstract: Fibronectinsisolated from human plasma @FN) and from the conditioned media of normal (N-cFN) and tumor (T-cFN) human cells were compared by cathepsin D digestion followed by immunostaining of released fragments with the monoclonal antibody 3E3, specific for the cell binding site. Two different staining patterns were obtained, one specific for pFN and N-cFN, the second common to fibronectins from the 3 different kinds of tumors studied. This indicates structural differences between N-cFN and T-cFN in the cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Owing to the availability of domain-specific MAbs, different fibronectin isoforms have been identified according to their tissue origin. Thus, there is fibronectin, termed oncofetal fibronectin, which is produced in high amount by fetal and tumor tissues but not adult normal tissues, and fibronectin produced by normal tissues and present in plasma (Matsuura and Hakomori, 1985;Borsi et al, 1985;Castellani et al, 1986;Zardi et al, 1987;Carnemolla et al, 1989;Loridon-Rosa et al, 1990). Sappino et al (1988) demonstrated the presence of a-smc-actin-positive myofibroblasts in human malignant breast tissues without, however, investigating the type of fibronectin they might produce.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the availability of domain-specific MAbs, different fibronectin isoforms have been identified according to their tissue origin. Thus, there is fibronectin, termed oncofetal fibronectin, which is produced in high amount by fetal and tumor tissues but not adult normal tissues, and fibronectin produced by normal tissues and present in plasma (Matsuura and Hakomori, 1985;Borsi et al, 1985;Castellani et al, 1986;Zardi et al, 1987;Carnemolla et al, 1989;Loridon-Rosa et al, 1990). Sappino et al (1988) demonstrated the presence of a-smc-actin-positive myofibroblasts in human malignant breast tissues without, however, investigating the type of fibronectin they might produce.…”
Section: Discussionmentioning
confidence: 99%
“…Neither depression in the synthesis (Mahdavi and Hynes, 1978Hynes, , 1979, nor increased degradation of Fn Mautner and Hynes, 1977), can apparently explain these differences. Though Fn produced by transformed cells may be altered by its glycosylation (Wagner ef al., 1981), phosphorylation (Ali and Hunter, 1981) and antigenic properties (Borsi et al, 1985), it binds to normal cells 1 2…”
Section: Discussionmentioning
confidence: 99%
“…EDB-FN is expressed in a variety of solid tumors and lymphomas [ 12 , 13 ], e.g., liver cancer, breast cancer, lung cancer, colorectal cancer, melanoma, Hodgkin and non-Hodgkin lymphoma, glioma, and head and neck cancer [ 14 ]. Additionally, EDB-FN is not only expressed in tumor cells but also in tumor-associated fibroblasts and neovascular endothelial cells in the tumor microenvironment [ 15 , 16 ]. EDB-FN is related to the stability of tumor tissue structure and tumor angiogenesis [ 17 ] and has a positive correlation with the progression and malignancy of various tumors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%